Optimisasi Penjualan Melalui Analisis Strategi Pemasaran dalam Manajemen Rantai Pasokan - Moh Fandy; Suci Larasati (Scimadly Publishing, 2023)
Every company has its unique strategy to market its products. The marketing strategy plays a vital role in ensuring the company's survival. If a company waits for an appropriate and suitable marketing strategy, it will impact consumer interest in the products it produces. A well-executed marketing strategy increases purchase intention. This study aims to examine how the Kipang Sisera Panyabung Mandailing Natal factory utilizes its marketing strategy to enhance sales volume and capture consumer interest. The research employs a qualitative approach, specifically the field research method, through observations and interviews conducted with the factory owners and employees. The research focuses on the Sisera kipang factory as the object of study. The analysis, utilizing SWOT analysis, reveals that the Kipang Sisera Factory has successfully increased sales volume through product diversification strategies, such as setting affordable prices, conducting promotions on specific days, maintaining good relationships with suppliers and consumers, and upholding product quality. Consequently, it can be concluded that the marketing strategy implemented by the Kipang Sisera factory effectively boosts sales volume, aligning with the appropriate marketing strategy.